PENGARUH OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN DI BURSA EFEK INDONESIA - Hasmi, Nurlaila; Pe'pan, Alpriani (Komunitas Manajemen Kompetitif, 2024)
The most important information for a company is information that comes from financial reports, so the submission of financial reports must be timely so that the information provided remains reliable and relevant. The aim of this research is to determine the effect of audit opinion on audit delay in trading sub-sector companies on the Indonesian Stock Exchange. The type of data used is quantitative data. The data source used is secondary data. The population in this study was 40 trading sub-sector companies on the Indonesia Stock Exchange for the 2017-2021 period. The sample used is all trading sub-sector companies on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique for this research is a purposive sampling technique, where samples are taken based on predetermined criteria and characteristics of the population. Based on these criteria, the sample used was 200 consisting of 40 companies and 5 years of financial reports. The analytical method used is descriptive and statistical analysis. The research results show that audit opinion has a significant effect on audit delay. Keywords: Audit Opinion, Audit Delay, Trading Sub-Sector Companies.